PS-P01-6: IMPLEMENTATION OF A BLOOD PRESSURE ACTION SHEET IN A RURAL COMMUNITY SETTING IN INDONESIA. (January 2023) - Rahmawati, Riana; Fauziyati, Ana; Sholawati, Aliza Ayu Puspita
Abstract : Objective: The Blood Pressure Action Sheet (BPAS) was developed as a written material that provides information about hypertension, records blood pressure monitoring, and facilitates communication among patients, community health workers, and healthcare professionals. The purpose of this study was to evaluate whether the BPAS would help to improve patient adherence to antihypertension medication. Adherence to medication is important in blood pressure control, which helps to reduce the risk of morbidity and mortality. Nonadherence to antihypertensive medications is a serious problem in both developed and developing countries. In this study, the perspectives of community health workers of the implementation of BPAS were also explored. Design and method: This was a community based study in Yogyakarta province, Indonesia. Members of the Integrated Health Service Post for the Elderly who were 45 years or older and had stage 2 hypertension were included in the study. This was a mixed methods study that included a pre post interventional study to assess whether medication adherence improved followed by a qualitative study to explore community health workers perspectives of the implementation of BPAS. Adherence to medication was assessed using the Indonesian version of the Medication Adherence Rating Scale (MARS) questionnaire. Adherence was compared from before to 3 months after the intervention. An in depth interview was conducted among community health workers. Results: One hundred eight patients fulfilled the inclusion criteria. Most were female (87%) and had a low education level. The average age was 67.2 ± 9.2 years. The MARS score was significantly higher after than before the intervention (20.5 ± 3.4 vs (18.7 ± 4.5, respectively; p < 0.05). The percentages of patients categorized as completely adherent (score 24 or 25) were 11.9% before and 19.6% after the intervention. The percentages of nonadherent patients (MARS score < 20) decreased from 46.2% before to 21.6% at 3 months after the intervention. Community health workers perceived the BPAS as user friendly and useful, and that it had potential for implementation in the Integrated Health Service Post for the Elderly. The challenges for implementation relate to its use for illiterate patients. Conclusion: The 3 month implementation of the BPAS improved patients adherence to antihypertension medication. Despite the positive findings, the adherence after the intervention was still not optimal. Further studies are needed to evaluate the effects of administering of the BPAS in different settings.